Andrzej Stasiuk, tekstowe figury doświadczenia - Kloch, Zbigniew (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
The aim of the article is to show the role of various metaphorical practices that are a dominant structural feature of Andrzej Stasiuk’s prose, used to construct his textual reality. Comparisons, metaphorical statements, and enumerations represent textual figures that transform the described experience of the world from the perspective of the speaking subject, subjectivising and constructing reality, rather than merely representing it. In both his novels and feuilletons, Stasiuk relates his experiences of the world in different temporal orders, constructing them on a textual level. Yet his thoroughly subjective prose preserves the conventions of realism. At the same time, Stasiuk quite often refers to the genre of the road novel, both in his fiction and in his journalism. Textual figures of experience are his basic means of describing the presented world.